2016
DOI: 10.1103/physreva.93.061603
|View full text |Cite
|
Sign up to set email alerts
|

Quantum filaments in dipolar Bose-Einstein condensates

Abstract: Collapse in dipolar Bose-Einstein condensates may be arrested by quantum fluctuations. Due to the anisotropy of the dipole-dipole interactions, the dipole-driven collapse induced by soft excitations is compensated by the repulsive Lee-Huang-Yang contribution resulting from quantum fluctuations of hard excitations, in a similar mechanism as that recently proposed for Bose-Bose mixtures. The arrested collapse results in self-bound filament-like droplets, providing an explanation to recent dysprosium experiments.… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
296
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 267 publications
(309 citation statements)
references
References 32 publications
13
296
0
Order By: Relevance
“…This demonstrates unambiguously that quantum fluctuations constitute the stabilizing mechanism. The conclusion we drew here is reinforced by numerical simulations reported in [36] of which we have recently become aware. Finally, we observe that the droplets have internal phase coherence.…”
Section: Prl 116 215301 (2016) P H Y S I C a L R E V I E W L E T T Esupporting
confidence: 64%
“…This demonstrates unambiguously that quantum fluctuations constitute the stabilizing mechanism. The conclusion we drew here is reinforced by numerical simulations reported in [36] of which we have recently become aware. Finally, we observe that the droplets have internal phase coherence.…”
Section: Prl 116 215301 (2016) P H Y S I C a L R E V I E W L E T T Esupporting
confidence: 64%
“…In these breakthrough experiments destabilization leads to the formation of stable droplets, that are only destroyed in a long time scale by three-body losses. Although first studies pointed to the possibility that large three-body conservative forces could stabilize the droplets [15,16], recent works have shown that the most plausible stabilization mechanism is due to quantum fluctuations [14,17,18], which play a similar role as that of surface tension in classical ferrofluids [19,20].…”
Section: Introductionmentioning
confidence: 99%
“…(110) as a function of the dimensionless parametersŨ =Ũ 2 +Ũ 3 andC = ε ddŨ2 for α = π/2. We compute the specific values of these parameters for a condensate of 164 Dy also considering as the 3-body contact interaction the value given in [12] (notice however that by using other values of U 3 , as the ones given in [69], the effect of such terms is anyway rather small). From Fig.…”
Section: B Dipolar Interactions In Magnetic Atoms and 3-body Contactmentioning
confidence: 99%
“…Recent experiments with dipolar BECs showed that under certain conditions where instability is expected from a standard Bogoliubov approach, dense clusters with many atoms can occur [61][62][63][64][65], which are expected to be superfluid [66]. Two interpretations have been proposed to explain the stabilization of this phase, namely the presence of weak 3-body interactions [11,12] and beyond mean-field effects (Lee-Huang-Yang type corrections) [67][68][69]. Motivated by these recent developments, we analyse in further detail the stability of uniform superfluids in the presence of long-range dipolar interactions and 2-and 3-body contact potentials.…”
Section: B Dipolar Interactions In Magnetic Atoms and 3-body Contactmentioning
confidence: 99%